Agent-Based Approaches in Economic and Social Complex Systems VI Post-Proceedings of The AESCS International Workshop 2009 - Chen, Shu-Heng.; Terano, Takao; Yamamoto, Ryuichi; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2011)
Agent-based modeling/simulation is an emergent approach to the analysis of social and economic systems. It provides a bottom-up experimental method to be applied to social sciences such as economics, management, sociology, and politics as well as some engineering fields dealing with social activities. This book includes selected papers presented at the Sixth International Workshop on Agent-Based Approaches in Economic and Social Complex Systems held in Taipei in 2009. We have 39 presentations in the conference, and 14 papers are selected to be included in this volume. These 14 papers are then grouped into six parts: Agent-based financial markets; Financial forecasting and investment; Cognitive modeling of agents; Complexity and policy analysis; Agent-based modeling of good societies; and Miscellany. The research presented here shows the state of the art in this rapidly growing field.
Keywords: Social sciences; Social sciences -- Data processing; Finance; Social sciences -- Methodology; Social Sciences; Methodology of the Social Sciences; Computer Appl. in Social and Behavioral Sciences; Financial Economics